2015
DOI: 10.1016/j.euroneuro.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive heterogeneity in adult attention deficit/hyperactivity disorder: A systematic analysis of neuropsychological measurements

Abstract: Attention Deficit / Hyperactivity Disorder (ADHD) in childhood is associated with impaired functioning in multiple cognitive domains: executive functioning (EF), reward and timing. Similar impairments have been described for adults with persistent ADHD, but an extensive investigation of neuropsychological functioning in a large sample of adult patients is currently lacking. We systematically examined neuropsychological performance on tasks measuring EF, delay discounting, time estimation and response variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
126
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 64 publications
(102 reference statements)
15
126
0
4
Order By: Relevance
“…First, we did not observe a distinct profile for reaction time variability in adults. Instead, patients in all three profiles were impaired on this measure, consistent with our earlier findings showing that reaction time variability is consistently increased in adults with ADHD, and has the largest effect size for distinguishing patients from controls (Mostert et al, in press). This also ties in with a recent meta-analysis showing moderate-to-large effect sizes for reaction time variability in children, adolescents, and adults with ADHD (Kofler et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…First, we did not observe a distinct profile for reaction time variability in adults. Instead, patients in all three profiles were impaired on this measure, consistent with our earlier findings showing that reaction time variability is consistently increased in adults with ADHD, and has the largest effect size for distinguishing patients from controls (Mostert et al, in press). This also ties in with a recent meta-analysis showing moderate-to-large effect sizes for reaction time variability in children, adolescents, and adults with ADHD (Kofler et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Coghill, Seth, and Matthews (2014) recently extended these findings by demonstrating that on each cognitive domain (working memory, inhibition, delay aversion, decision making, timing, and variability), only a minority of children with ADHD performed deficiently, despite significant group-level effects on all domains. In line with these studies, our own work has shown that adult ADHD patients are impaired in multiple cognitive domains (attention, working memory, and delay discounting), but with moderate effect sizes and with large variability in the number of neuropsychological tasks on which patients performed deficiently (Mostert et al, in press). This indicates that cognitive heterogeneity is also apparent in adults with ADHD.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Second, ADHD is characterized by large phenotypic heterogeneity, reflected by differences between subjects in ADHD subtype, symptom severity, and cognitive impairments (Coghill et al, 2014, Mostert et al, 2015, Nigg et al, 2005). This large phenotypic heterogeneity in ADHD might be related to a possible large heterogeneity in the underlying neurobiology.…”
Section: Discussionmentioning
confidence: 99%